Dissecting Electoral Support for the Far Right: A Comparison between Mature and Post-Communist European Democracies. Issue 1 (4th January 2022) - Brils, Tobias; Muis, Jasper; Gaidytė, Teodora
Abstract: This article investigates three explanations for electoral support for the far right – 'cultural backlash', 'economic grievances' and 'protest voting' – in a novel way. Our main contribution is that we contrast far-right voters with voters of centre-right parties, traditional left-wing parties and abstainers. Equally innovative is the comparison between mature and post-communist democracies. Using European Social Survey data (2014–16), we conclude that anti-immigration attitudes are most important in distinguishing far-right voters from all other groups. Yet, these differences are significantly smaller in Eastern Europe. Furthermore, far-right voters are not the so-called socioeconomic 'losers of globalization': this is only true when compared with centre-right voters. Concerning protest voting, distrust of supranational governance particularly enhances far-right voting. Overall, our study concludes that more fine-grained distinctions pay off and avoid misleading generalizations about 'European far-right voters' often presented in public debates.